Suppression of crosstalk in multielectrode arrays with local shielding - Naughton, J. R.; Varela, J. A.; Connolly, T. J.; Shepard, S.; Dodge, T. E.; Kempa, K.; Burns, M. J.; Christianson, J. P.; Naughton, M. J. (Frontiers in Nanotechnology, 2022)
Electrical crosstalk can constrain the performance of multi-electrode arrays in electro- and neurophysiology, in terms of both stimulation and recording. This is especially so at high electrode density, desirable for spatiotemporal mapping of bioelectrical signals from multiple cells. Channel interference due to crosstalk is currently only partially addressed, via continuous interleaved sampling or post-data acquisition spike sorting. Here, we show that a locally-shielded electrode architecture significantly suppresses crosstalk, and enables multi-site recording at high electrode density without the need for spike sorting. Arrays of shielded electrodes, prepared by micro- and nanofabrication techniques in a vertically-oriented coaxial geometry, demonstrate at least a 400 times improvement in spatial density over the unshielded case.